2022
DOI: 10.1039/d2re00014h
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitrogen fixation in the presence of a liquid interface: role of OH radicals

Abstract: Physical backgrounds of nitrogen fixation process in a nanosecond pulsed discharge in the presence of a plasma/liquid interface are reported. The role of OH radicals and O atoms in NO...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…[31] Building upon existing research, future investigations may focus on inhibiting reactions between oxidative species (such as OH radicals and O atoms) and nitrogen species, as well as suppressing hydrogen evolution reactions, to further enhance ammonia synthesis selectivity. [93] Research into the generation of different reactive nitrogen species and their respective reactivity with oxidants and reductants could lead to breakthroughs. [94] This exploration can provide insights into adjusting reaction conditions to promote the formation of active nitrogen species favorable for ammonia synthesis.…”
Section: Reaction Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…[31] Building upon existing research, future investigations may focus on inhibiting reactions between oxidative species (such as OH radicals and O atoms) and nitrogen species, as well as suppressing hydrogen evolution reactions, to further enhance ammonia synthesis selectivity. [93] Research into the generation of different reactive nitrogen species and their respective reactivity with oxidants and reductants could lead to breakthroughs. [94] This exploration can provide insights into adjusting reaction conditions to promote the formation of active nitrogen species favorable for ammonia synthesis.…”
Section: Reaction Selectivitymentioning
confidence: 99%
“…These radicals then react with reactive nitrogen species, resulting in the production of nitrogen oxides that dissolve in water and ultimately form nitrate and nitrite species through a series of reactions. While this type of reactions is acceptable for nitrogen fixation purposes, it presents a challenge for the plasma‐assisted ammonia synthesis as it competes with the desired reaction, utilizing reactive nitrogen species and generating byproducts that reduce the ammonia yield [93] . Therefore, improving the selectivity of the plasma nitrogen‐water system has become a key objective in the ammonia synthesis research.…”
Section: Plasma‐assisted Synthesis Of Nh3 From N2 and H2omentioning
confidence: 99%
“…Currently, relevant studies have been carried out to reveal the chemical mechanism of NO x generation from NTPNF through experiments or simulations. Vibrational excitation of N 2 and O 2 molecules provides the energy required to overcome the activation barrier for the nonthermal Zeldovich mechanism. ,,,, It involves two crucial steps: the reaction of excited-state N 2 (v) molecules and O• radicals (R1) and the reaction of excited-state O 2 (v) molecules to N• radicals (R2) (where v represents vibrationally excited states). Furthermore, the participation of water vapor can further extend the Zeldovich mechanism: the N• radical forms NO (R3) by reacting with the OH produced by hydrolysis. For the catalytic mechanism, some studies have proposed the Eley–Rideal (E-R) and Langmuir–Hinshelwood (L-H) mechanisms with density functional theory (DFT) calculations, ,, but the reasons for choosing these two mechanisms or the modes for their actions were not investigated. Furthermore, these mechanism studies do not fully take into account the coupling with plasma, which is essential for developing a theoretical basis for the design of discharge devices and catalysts in the plasma. N 2 false( normalv false) + O NO + N O 2 false( normalv false) + N NO + O N + OH NO + H …”
Section: Introductionmentioning
confidence: 99%
“…Herrmann et al [23] studied the influences of peak voltage and discharge gap distance on pulsed discharge behavior over the liquid surface. Gromov et al [24] reported the physical process at the gas-liquid interface in a single pulse mode and high-frequency burst. Xu et al [25] compared the pulsed discharge plasma and sinusoidal discharge plasma, the results showing that nanosecond pulsed discharge plasma has lower gas temperature and higher efficiency of bacterial inactivation in liquid than that of the sinusoidal discharge plasma.…”
Section: Introductionmentioning
confidence: 99%